ANALYSIS OF CAUSING FACTORS ON THE APPEARANCE OF HABS IN COASTAL WATER OF MAKASSAR - Tambaru, Rahmadi; La Nafie, Yayu A. La Nafie; Junaidi, Astrid W. (Jurnal Ilmu Kelautan SPERMONDE, 2018)
HABs were types of phytoplankton considered dangerous in the sea. Its appearance was triggered by an increase in nutrients and the presence of physical and chemical factors in the optimal conditions to support its growth. For that reason, research on the analysis of the causes of the emergence of HABs in the coastal waters of Makassar has been carried out. The implementation is carried out from March to June 2017 using non-experimental methods. The results showed that there were seven types of HABs, such as Protoperidinium, Gymnodinium, Ceratium, Prorocentrum, Gyrodinium, Gonyaulax, and Dinophysis. That types from the Dinophyceae Class. The appearance of the types of HABs was due to the influence of temperature with the relationship were very strong and positive.